Rancang Bangun Sistem Informasi Evaluasi Pembelajaran Menggunakan Framework React dan Laravel Berbasis Website untuk Memudahkan Penilaian Pengajar dan Fasilitas Di PT Aksesindo Semesta Nusantara - Hafiz Fahmi; Muhammad Rafli; Ade Syahrul Ramadhani; Sutriyono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
PT Aksesindo Semesta Nusantara is an educational institution that offers tutoring services to prepare participants for the selection of CPNS (National Civil Servant Candidates), PPPK (National Civil Service Candidates), civil service schools, the Indonesian National Armed Forces (TNI), the Indonesian National Police (Polri), and higher education. Measuring learning success requires a systematic system to collect feedback from participants regarding instructors and classes to ensure data can be managed centrally and efficiently. To address this issue, a Website-Based Tutoring Review Information System was developed using the Waterfall approach. The goal of this system is to provide a digital evaluation tool that facilitates participants in providing assessments and assists management in monitoring teaching quality quickly and accurately. The design process involved observation, documentation studies, and system requirements analysis, which was then built using the Laravel and React frameworks and a MySQL database. The result of this practical activity is a website-based review system that allows participants to provide ratings and feedback via a link or QR Code without having to log in. This system has the ability to manage class session data, instructors, assessments, and participant feedback in an integrated manner. With this system, the learning evaluation process becomes more effective and efficient, and supports the improvement of the quality of educational services at PT Aksesindo Semesta Nusantara.